2015
DOI: 10.1128/aac.01492-15
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profiles of Staphylococcus aureus Isolates Recovered from Humans, Environmental Surfaces, and Companion Animals in Households of Children with Community-Onset Methicillin-Resistant S. aureus Infections

Abstract: Our objective was to determine the antibiotic susceptibility profiles of Staphylococcus aureus isolates recovered from 110 households of children with community-onset methicillin-resistant S. aureus (MRSA) infections. Cultures were obtained from household members, household objects, and dogs and cats, yielding 1,633 S. aureus isolates. The S. aureus isolates were heterogeneous, although more than half were methicillin resistant. The highest proportion of MRSA was found in bathrooms. The majority of isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…We identified that 68% MRSA isolates from the home environment were susceptible to (21). The finding of a protective role for clindamycin use by humans or domestic animals in the household is consistent with a prior report of a study with this cohort that the use of clindamycin is associated with both the earlier clearance and the lower persistence of colonization among the index patients (28,29).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We identified that 68% MRSA isolates from the home environment were susceptible to (21). The finding of a protective role for clindamycin use by humans or domestic animals in the household is consistent with a prior report of a study with this cohort that the use of clindamycin is associated with both the earlier clearance and the lower persistence of colonization among the index patients (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…The literature on risk factors that may contribute to multidrug and/or mupirocin resistance in the environmental CO-MRSA reservoir is limited. One prior study charac- terized the antimicrobial susceptibility among S. aureus isolates collected from household inhabitants, environmental surfaces, and the pets of children with CO-MRSA, but that study did not evaluate the risk factors associated with the prevalence of MDR or mupirocin resistance in the home environmental MRSA reservoir (21). Although the overall rates of mupirocin resistance were low, our study demonstrated that the household environment can act as a reservoir of mupirocin-resistant MRSA, that the presence of Mup r MRSA in households has the potential to be associated with treatment failure due to recolonization or persistent colonization, and that the use of mupirocin in decolonization treatment has the potential to be associated with incident low-level mupirocin resistance in the home environmental MRSA reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study done by Arali et al, 4.9% resistance was observed for vancomycin, whereas the isolates were 100% sensitive to vancomycin in a study done by Morelli et al 29,30 Our study is also in accordance to the study of Radhakrishna et al where the sensitivity of S. aureus isolates to vancomycin and linezolid was 100%. 4 In this study, the resistance of S. aureus isolates to penicillin was 100% (Figure 3) which is similar to the findings of Radhakrishnan et al 4 Among the MRSA isolates, 100% sensitivity to vancomycin and linezolid was observed (Figure 4) in accordance with the findings of Radhakrishnan et al However, sensitivity to vancomycin was 84.3% in a study done by El Aila et al 31 As disc diffusion test is not reliable for vancomycin we determined MIC of the MRSA isolates by automated Vitek 2 system.…”
Section: Resultssupporting
confidence: 81%
“…Morelli et al in a study on 1,633 unique S. aureus isolates reported. All isolates were susceptible to trimethoprim sulfamethoxazole, linezolid, ceftaroline, and rifampin, while the majority of isolates were susceptible to clindamycin, tetracycline, and mupirocin [19]. Also, Sun et al conducted a descriptive study in China on specific molecular and epidemiological characteristics of S. aureus in patients in Xinyang, China.…”
Section: Discussionmentioning
confidence: 99%